ANALISIS DESKRIPTIF KELENGKAPAN PENGISIAN DAN KETERLAMBATAN PENGEMBALIAN BERKAS REKAM MEDIS RAWAT INAP DI RSUD dr. R. SOEDARSONO KOTA PASURUAN - Ratna Ratna; Muhammad Malik Ibrahim; Ika Puspita Sari (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
The number completeness of filling and returning medical record files on time in Indonesia is still relatively low. One of them happened at RSUD dr. R. Soedarsono, Pasuruan City. Where the results of the preliminary study showed in January, 83% incomplete medical record files and 17% complete medical records. Meanwhile, the return of medical record files was 79% late and 21% not late. The purpose of this study  to analyze the completeness of filling and delay in returning inpatient medical record files at Soedarsono Hospital, Pasuruan City. This type of research is quantitative descriptive with cross sectional approach. The sample of this study amounted 161 medical record files of BPJS patients were returned from inpatient room to the assembly unit. Data collection techniques using checklists and data analysis using univariate analysis. The results showed 28.6% (46 files) of complete medical record files, and 71.4% (115 files) were incomplete. Meanwhile, the return of medical record files was 55.9% (90 files) late and 44.1% (71 files) not late. The conclusion of this study is the completeness of filling and delay in returning medical record files at the dr.R.Soedarsono Hospital, Pasuruan City is still quite high.